Evaluating the potential of bio-cementing pond ash using Microbially Induced Calcite Precipitation (MICP) - Dhriyan S.S.; Verma A.K.; Prasad A. (My University, 2025)
Thermal power plants globally encounter substantial challenges in storing and managing coal ash. The conventional method of wet disposal in ponds consumes extensive land areas and has an adverse effect on the environment. Fluctuations in temperature and moisture across the seasons can lead to the release of dust, which poses a risk to the environment. Cases of breaching ash impoundment prompted the exploration of solutions to utilize pond ash (PA) on a large scale. This problem can be mitigated by incorporating ash into significant structural and geotechnical earthworks. However, a few constraints and uncertainties remain over its characteristics and assessment. This study aims to investigate the efficacy of microbial induced calcite precipitation (MICP) to enhance the geotechnical and morphological properties of PA. The applicability of two ureolytic bacteria, Bacillus Sphaericus (BS) and Bacillus Megaterium (BM) for stabilizing pond ash is assessed. Laboratory findings demonstrated the effectiveness of MICP in enhancing the properties of PA, with unconfined compressive strength (UCS) improving up to 1105 kPa and hydraulic conductivity reducing by 91 % for BS-treated PA. Optimal performance was achieved using 0.75 Molarity Cementing Solution, which also significantly improved CBR values to 19 % (unsoaked) and 15 % (soaked). It is also observed that the molarity of the cementing solution and number of treatment days play a vital role in calcite production, hence the strength gain. The SEM analyses of the microstructure and XRD analyses of mineralogy revealed the calcium carbonate precipitation. The study underscores the viability of MICP as a sustainable approach to address pond ash challenges as geo-material. © 2025 Elsevier Ltd